Application of a phase-field model to ferroelectrics - Renuka-Balakrishna, A (2016)
The current work uses a phase-field model to design nanoscale ferroelectric device concepts and to explore nanoscale ferroelectric behaviour. The results are expected to serve initial steps for nanoscale experimentation and to assist in the industrial application of ferroelectrics. The use of ferroelectrics in nanoscale devices such as sensors or energy harvesters has increased in recent times. This has advanced research interests in nanoscale ferroelectric properties. In the current study, a phase-field model is used as a research tool to explore nanoscale behaviour of barium titanate. The model is first used to design and optimize nano-actuator concepts that generate actuation strains ~0.45%. This strain is four times as large as the strain offered by piezoceramic actuators in market. Next, the model is used to describe how scaling and surface conditions affect the formation of nanoscale polarization patterns, such as vortices. The results demonstrate the dominant effect of surface conditions and explain experimental observations of phase, tetragonality and polarization patterns in ferroelectric nanoparticles. The phase-field model is next extended to three dimensions and is used to test the stability of nanoscale periodic polarization patterns. The results describe the internal stress and electric fields developed in these patterns, and illustrate a mechanism of how complex polarization patterns can be formed under external strain or electric fields. Here, a conceptual design of an energy harvester is also explored. The current work explores the application of a phase-field model as a design tool to develop nano-actuator and energy harvester concepts. The results on actuation/harvester cycle and the design parameter optimization would assist in developing device prototypes and eventually benefit in industrial fabrication. The phase-field model extended to three dimensions contributes to the study of domain patterns with out-of-plane polarizations and will assist in engineering a more realistic ferroelectric device. The results on the effects of scaling, surface energy and external loads on nanoscale polarization patterns, explains prior experimental observations of polarization patterns and provide useful insights on how to engineer domain configurations for nanoscale applications. Finally, the results motivate research towards developing prospective nanoscale applications from other smart materials, such as relaxors and ferromagnets.